The health sector development 1990-1995. the operative collapse and silent sanitary reform - Arroyo, Juan (1996)
We set up that the health sector, during the worst period of the crisis between 1988 and 1992, regarding to the goverment omission as3 well as the operative collapse of public services, started a big passive transformation of the peruvian sanitary system - a silent sanitary reform -, where the actual health policy did not emerge due to legal regulations but as a result of a spontaneus clash of the sanitary plaintiffs. Then, since 1993 a second phase of slow restoring began, but still taking the wrong turning, starting to return toward the preceding recession and chaotic trends. But in neither of these two phases, this silent reform that developed as a disgoverned reform process of the peruvian sanitary system, has detained. The health sector has gone through nine big changes under this non systemic or accumulative reform: 1) The gradual reconvertion of public hospitals (Public Health Ministery) into semi-private institutions; 2) Multiplication of crossed pressures on health demands and their continual resegmentation according to changes in services supply; 3) TYhe peruvian social security reform during the 1990 - 1995 quinquennium, a forced gear modernization; 4) The reform of the grat private sector in health with private insurance with its recent operative modalities; 5) The arousal of a new private subsector as a non-profit making institution as well as the church and NGOs; 6) The change of medical work development and the later passing from an unemployment crisis to full emplymentness; 7) The duality of both, medical care and taking refuge of unprotected population in both, self-medication prescription and traditional medicine; 8) The finnancial aid and international cooperation rising since 1993; 9) The reinforcement of a  peripherical net and the display of several partial iniciatives (Basic Health for Everyone, projects and programs), all of them expressions of reform but still without a formal reform.